(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This Article is focused upon constitutionality of section 497 in the IPC which deals with the offence of adultery. ’The Committee on the State of Women in India’ has condemned the judicial response to the criminal offence of adultery (CSWI). Bigamy is illegal under the law (Sec 494 IPC). Even if we agree that the law is unbiased in that both husband and wife cannot sue each other for the criminal offence of adultery, the demand for punishment for the wife alone appears baseless as long as the husband is not found guilty of the criminal offence of adultery; and it seems most unfair for a man to demand from a wife the chastity he does not practise. Criminal communication can result in a maximum 5-year prison sentence, as well as a fine or both. The constitutional legality of this clause has been questioned in several cases, and women’s rights advocates have repeatedly contested the retention of the provision about free love. Despite the fact that the laws were originally created to safeguard women and make only those in dangerous situations accountable, they instead serve to spread the societal view that women are weak, have no thought of their own, and hence must be protected by males. On occasions over one, the constitutions vires of section 497 was challenged within the Supreme Court on the ground, inter alia, that it by creating solely a person accountable for free love and mandating a court that the slut wife be not admonished as associate accessory discriminates in favour of ladies and against men only on the bottom of sex, and thereby goes against the spirit of equality embodied within the constitution.After learning all of the above, the author has come to the conclusion that the errant mate’s husband/wife should not only be allowed to seek divorce from the other life partner, but also to initiate legal proceedings with the goal of establishing criminal liability for the "outsider" who ruined the wedding.The methodology used in the present Article is mixture of primary as well as secondary research.